"Applying anatomy to something I care about": Authentic inquiry learning and student experiences of an inquiry project. Issue 6 (4th April 2017) - Anstey, Lauren M.
Abstract : Despite advances to move anatomy education away from its didactic history, there is a continued need for students to contextualize their studies to make learning more meaningful. This article investigates authentic learning in the context of an inquiry‐based approach to learning human gross anatomy. Utilizing a case‐study design with three groups of students ( n = 18) and their facilitators ( n = 3), methods of classroom observations, interviews, and artifact collection were utilized to investigate students' experiences of learning through an inquiry project. Qualitative data analysis through open and selective coding produced common meaningful themes of group and student experiences. Overall results demonstrate how the project served as a unique learning experience where learners engaged in the opportunity to make sense of anatomy in context of their interests and wider interdisciplinary considerations through collaborative, group‐based investigation. Results were further considered in context of theoretical frameworks of inquiry‐based and authentic learning. Results from this study demonstrate how students can engage anatomical understandings to inquire and apply disciplinary considerations to their personal lives and the world around them. Anat Sci Educ 10: 538–548. © 2017 American Association of Anatomists.